(untitled) (Ius Novum, 2021)
The gloss discusses legal consequences of the approval of a general plan of a public airport. It concerns the necessity of suspending proceedings in the case of determining the conditions of investment developments in the area covered by a general plan until the zoning scheme is adopted in accordance with this general plan. Approving of the stance expressed in the judgement of the Supreme Administrative Court, the gloss also presents calls for amendments to the provisions of Act: Aviation Law concerning general plans of airports, as well as the related provisions concerning areas limiting aviation obstacles. The author’s arguments are based on the distinction between possible legal instruments laid down in aviation law regulations in order to ensure the development of aviation infrastructure.